MANAJEMEN STRES - Adiyono Adiyono (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
This research aims to investigate various stress management strategies documented in the literature related to the educational environment, especially for students and teaching staff. The research method used is library research, with a focus on a collection of articles, books and scientific journals that discuss stress management initiatives in the educational context. Through literature analysis, this research details various approaches that have been proposed and implemented to reduce stress in schools. It is hoped that the findings from this research will provide an in-depth understanding of the efforts that have been made to manage stress in the educational environment and provide a basis for developing more effective stress management strategies in the future. The implications of this research can provide guidance for educational practitioners in improving the emotional well-being of students and teaching staff.